Pemberdayaan Pedagang Sayur Keliling Melalui Program “Abang Sayur” dalam Upaya Peningkatan Penjualan di Era Covid-19 - Dyanasari, Dyanasari; Trianawati, Anis; Arvianti, Eri Yusnita (Universitas Tribhuwana Tunggadewi Malang, 2022)
This community service program aims to provide counseling about increasing sales of vegetable products through the concept of